The Effect of the Er:YAG Laser and MI Paste Plus on the Treatment of White Spot Lesions - Yassaei, Soghra; Motallaei, Mohammad nima (Journal of Lasers in Medical Sciences, 2020)
Introduction: White Spot Lesions (WSLs) occurring after orthodontic treatment lead to patient dissatisfaction and aesthetic problems. The role of calcium-phosphate demineralization systems and Er:YAG laser in the treatment of these lesions has been recently taken into account. This study was aimed to investigate the effect of Er:YAG laser and MI-Paste Plus on the treatment of WSLs. Methods: A total of 65 premolars extracted due to orthodontic treatment were studied in this research. To create enamel lesions, the teeth were placed in a demineralizing solution. The teeth were then randomly divided into five groups (n=13). First group: control, second group: saliva, third group: MI Paste Plus, fourth group: Er:YAG laser, and fifth group: MI Paste together with Er:YAG laser. The teeth were kept in artificial saliva between treatment processes and was exchanged daily. The teeth were sectioned longitudinally by a disc from the middle of the exposed enamel and each section was mounted in polyester resin. The surface of the samples was serially polished and the microhardness of the teeth was measured at depths 0, 50, 100, and 150 µm. Results: The microhardness was significantly higher in fifth group than other groups at all depths (P<0.05). The microhardness of fourth group was significantly higher than that of the three other groups at depth 150 µm (p<0.05). The microhardness of third group was significantly higher than that of the control group at depth 0 µm (p<0.0001). Conclusions: The combined application of the Er:YAG laser and MI Paste Plus is effective in the treatment of WSLs.